The Evolution of E-Government in Malaysia: Institutional Mechanisms and Public Service Transformation at the Federal and State Levels - Mohammed Yasin, Nazreena; Rohana Abdul Hamid (Human Sustainability Procedia, 2025)
The evolution of e-government in Malaysia has emerged as a cornerstone in reforming public administration since the inception of the Multimedia Super Corridor (MSC) in 1996. Over the years, the government has introduced a series of transformative initiatives aimed at enhancing service delivery, transparency, and administrative efficiency. This conceptual paper examines the historical progression, institutional structures, and services embedded within Malaysia’s e-government framework. Anchored by institutions such as the Malaysian Administrative Modernisation and Management Planning Unit (MAMPU), the National Institute of Public Administration (INTAN), and the Malaysia Digital Economy Corporation (MDEC), these efforts have reshaped governance through technological innovation. Drawing from paradigms of public administration, including Old Public Administration, New Public Management, and New Public Service, this paper analyses how Malaysia’s digital governance evolved from hierarchical bureaucratic practices to more citizen-centric and participatory models. While significant strides have been made, challenges remain, particularly in bridging the digital divide, fostering state-level adoption, and enhancing data security. This study concludes with reflections on the importance of institutional coordination, policy continuity, and sustained investment to ensure the long-term success of e-government in Malaysia.